2000
DOI: 10.1063/1.481167
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon coupling dynamics in very small (between 2 and 8 nm diameter) Au nanoparticles

Abstract: Ultrafast laser experiments were used to study electron-phonon coupling in Au nanoparticles in the 2.5 to 8 nm size range in aqueous solution. The electron-phonon coupling constants for these samples were found to be independent of the particle size. This is attributed to a weak interaction between the electron gas and the surface phonon modes in Au. Calculations were performed which show that the coupling between the hot electrons and the surface accounts for less than 10% of the total electron energy losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
232
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(275 citation statements)
references
References 39 publications
28
232
4
Order By: Relevance
“…This effect has been observed earlier and can be rationalized by the fact that the electronic heat capacity is also dependent on the initial electronic temperature rise [16,17]. Fig.…”
Section: Resultsmentioning
confidence: 78%
“…This effect has been observed earlier and can be rationalized by the fact that the electronic heat capacity is also dependent on the initial electronic temperature rise [16,17]. Fig.…”
Section: Resultsmentioning
confidence: 78%
“…However, for the electron-phonon relaxation dynamics this is not observed experimentally. Using a theory developed by Belotskii et al (107), Hartland and coworkers (108) showed that the coupling constant between the electrons with acoustic and capillary modes of the surface phonons is determined by the ratio of the number of valence electrons in the atom to the atomic mass of the metal. Because of the small number of the valence electrons in gold (only one electron) combined with a large atomic mass, the contribution of electron-surface scattering to the overall electron-phonon scattering cross section is very small.…”
Section: Ultrafast Dynamics: Electron-phonon and Phonon-phonon Relaxamentioning
confidence: 99%
“…24) On the other hand, the energy transfer in the nanoparticle also occurs thorough electron-surface interactions, which couple an acoustic surface mode and a capillary surface mode with electrons. 25,28,29) The acoustic and capillary mode coupling constants, g A and g C respectively, are given by 25) …”
Section: Resultsmentioning
confidence: 99%
“…The relaxation behavior in the nanoparticle can be expressed by the two-temperature model, which describes the energy exchange between the electrons and phonons in nanoparticles by the coupled equations. [22][23][24] In the limit of low pump power, where the change in lattice temperature can be neglected, time evolution of the electron temperature is given by 25,26) γ…”
Section: Resultsmentioning
confidence: 99%